2022
DOI: 10.3390/cancers14163870
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Studies to Evaluate Receptor-Specific Radioligand Binding in the CAM Model by PET and MR Imaging

Abstract: Inhibition studies in small animals are the standard for evaluating the specificity of newly developed drugs, including radiopharmaceuticals. Recently, it has been reported that the tumor accumulation of radiotracers can be assessed in the chorioallantoic membrane (CAM) model with similar results to experiments in mice, such contributing to the 3Rs principles (reduction, replacement, and refinement). However, inhibition studies to prove receptor-specific binding have not yet been performed in the CAM model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In another study, it was reported that radiotracers specifically accumulate in the ovografts and can be followed in the CAM model using positron emission tomography and magnetic resonance scanning [7]. Moreover, the specific target-binding of radiopharmaceuticals was assessed in MRI using specific blocking agents [8]. Consequently, the authors suggested the CAM model as an effective pre-screening assay to detect the bio-distribution of novel radiolabeled compounds saving animal experiments in mice.…”
Section: Survey For Papers In This Special Cam Issuementioning
confidence: 99%
“…In another study, it was reported that radiotracers specifically accumulate in the ovografts and can be followed in the CAM model using positron emission tomography and magnetic resonance scanning [7]. Moreover, the specific target-binding of radiopharmaceuticals was assessed in MRI using specific blocking agents [8]. Consequently, the authors suggested the CAM model as an effective pre-screening assay to detect the bio-distribution of novel radiolabeled compounds saving animal experiments in mice.…”
Section: Survey For Papers In This Special Cam Issuementioning
confidence: 99%
“…In the last 10 years, the interest of the nuclear imaging community in this model has increased [ 36 ]. Imaging studies were performed using different radiotracers, cancer models, and imaging modalities [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. There are already initial studies showing the comparability of the in ovo model to mice [ 40 , 45 ], suggesting good transferability of results to other animal species.…”
Section: Introductionmentioning
confidence: 99%